Bank Customers’ Perception Towards Debit Cards in Sholinganallur, Chennai - Dr. R. Ilavenil, Dr. S. Prasanth, Shahina Begam, Dr. P. Nivetha, Dr. Meera (Journal of Informatics Education and Research, 2024)
The term "plastic money" refers to the sturdy plastic cards that are used in daily life in place of real banknotes. One sort of innovation that allows consumers to access banking services without having to limit their use to official banking hours is the use of plastic cards. consumers can utilize these services simply by possessing the card that the bank issues. They are available in a variety of formats, including shop cards, credit cards, debit cards, and pre-paid cash cards. For the study, both primary and secondary data were employed. In Sholinganallur, Chennai, bank clients using debit cards provided the primary data. There are 300 people in the study's sample. ANOVA, factor analysis, and descriptive statistics are the instruments utilized in the analysis. According to the study's findings, 55% of clients of public sector banks in Sholinganallur and 72% of holders of plastic money at private sector banks indicated satisfaction with the type and caliber of services they received. The paper seeks to examine how Sholinganallur consumers view debit cards.